Distinct role of subcomplexes of the COPI coat in the regulation of ArfGAP2 activity - Pevzner, Irit; Strating, Jeroen; Herrmann, Alexia; Brügger, Britta; Wieland, Felix T. (Traffic, 2012)
COPI vesicles serve for transport of proteins and membrane lipids in the early secretory pathway. Their coat protein (coatomer) is a heptameric complex that is recruited to the Golgi by the small GTPase Arf1. Although recruited en bloc, coatomer can be viewed as a stable assembly of an adaptin-like tetrameric subcomplex (CM4) and a trimeric ‘cage’ subcomplex (CM3). Following recruitment, coatomer stimulates ArfGAP-dependent GTP hydrolysis on Arf1. Here, we employed recombinant coatomer subcomplexes to study the role of coatomer components in the regulation of ArfGAP2, an ArfGAP whose activity is strictly coatomer-dependent. Within CM4, we define a novel hydrophobic pocket for ArfGAP2 interaction on the appendage domain of γ1-COP. The CM4 subcomplex (but not CM3) is recruited to membranes through Arf1 and can subsequently recruit ArfGAP2. Neither CM3 nor CM4 in itself is effective in stimulating ArfGAP2 activity, but stimulation is regained when both subcomplexes are present. Our findings point to a distinct role of each of the two coatomer subcomplexes in the regulation of ArfGAP2-dependent GTP hydrolysis on Arf1, where the CM4 subcomplex functions in GAP recruitment, while, similarly to the COPII system, the cage-like CM3 subcomplex stimulates the catalytic reaction.